Macroprolactinoma in a 14-Year-Old Girl in the Northeast of Iran: A Case Report - Shakeri, Habibe Sadat; Mollazadeh, Samaneh; Monemi, Alireza (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2024)
Prolactinoma is frequently found not only in females but also in males with abnormal reproductive and/or sexual function. Patients typically complain about amenorrhea and infertility because of anovulation. Approximately 15% to 20% of cases of secondary amenorrhea are caused by prolactinemia. Galactorrhea may occur simultaneously, before or after menstrual disorders, and sometimes it may not be clinically obvious, or only detected by breast examination. We reported a case of a 14-year-old girl who presented primary amenorrhea accompanied by frequent headaches and blurred vision. Hormonal tests showed severe hyperprolactinemia (prolactin [PRL] concentration: 1,570 ng/ml). Further tests confirmed a mass in the pituitary with an extension to the left parasellar and suprasellar regions. Some parts of the sella turcica tumor were removed by transcranial surgery. During the follow-up, the clinicopathological examinations revealed the patient had hyperprolactinemia. Clinicians should be aware of the diagnostic and therapeutic problems regarding the management of hyperprolactinemia.
Keywords: macroadenoma; prolactinoma; pituitary; amenorrhea; sella turcica